2017
DOI: 10.1016/j.polymer.2017.02.094
|View full text |Cite
|
Sign up to set email alerts
|

Novel hydrogels containing Nafion and poly(ethylene oxide) based block copolymers

Abstract: We present a novel family of biocompatible hydrogels containing Nafion and poly(ethylene oxide) based block copolymers. In aqueous environment, thermodynamically stable ionomercopolymer complexes are formed, as evident by light scattering and quartz crystal microbalance experiments. Moreover, incorporation of Nafion dramatically modifies the phase behaviour and the rheological properties of copolymer hydrogels. The hybrid systems not only undergo sharp and thermally reversible sol-gel transitions below the bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…The nitrate ions of sodium and potassium have great impact on the viscosity and tend to minimize this effect and finally become aligned which no further change in viscosity occurs. The same trend was reported by Volk and his co-workers [31].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The nitrate ions of sodium and potassium have great impact on the viscosity and tend to minimize this effect and finally become aligned which no further change in viscosity occurs. The same trend was reported by Volk and his co-workers [31].…”
Section: Resultssupporting
confidence: 90%
“…Similarly, the particle size, shape and particle distribution have greater effect on the viscosity of the polymeric composite. As the cationic and ionic size of KNO 3 and NaNO 3 are small, so these ions move freely without facing any hindrance [31]. It can be seen from our results that pure blend PANI-PEO has lower viscosity at all temperatures.…”
Section: Resultsmentioning
confidence: 63%
“…4. In previous studies it has been demonstrated that complexation of Nafion with peptides, 34 polymers 30,35,36 and metal–organic frameworks 37 is driven by electrostatic interactions, hydrogen bonding and the hydrophobic effect.…”
Section: Resultsmentioning
confidence: 99%
“…Upon water exposure, Nafion’s surface is reorganised with the sulphonic groups to be turned into the aqueous phase, a mechanism that gives rise to a large water contact angle hysteresis [24]. Owing to its amphiphilic nature Nafion has been shown to bind not only with charged polymers such as poly (oxyethylene) [25] and poly (oxypropylene) based diamines [26], but also with non-ionic surfactants via hydrogen bonding, hydrophobic interactions [27,28,29].…”
Section: Resultsmentioning
confidence: 99%